Overview of High 120 m Concrete Dam Bratsk Hydroelectric Power Plant: A Recent Perspectives - Mark A. Sadovich; Tatyana F. Shlyakhtina; Sofia M. Ginzburg; Alexander M. Yudelevich (Theory and Applications of Engineering Research Vol. 1, 2023)
This chapter defines about present state of high 120 m concrete gravity dam of the Angara Bratsk hydroelectric power plant. The state of the concrete dam is estimated based on the results of continuous supervision performed by site personnel as well as periodic monitoring. Advances in technology will bring new and better means and methods for monitoring, but the broad principles outlined herein should have enduring value. These guidelines are intended to be educational, providing a handy source of information about instrumentation and measurements for monitoring dam performance. A thorough examination of the concrete was conducted on a few key dam components that were chosen based on the categorization of the relationships within the "concrete-environment" system. It has been suggested to combine full-scale tests and core-sampling in the intricate study of concrete. The centennial existence of concrete dams (apart from surface areas) appears to be assured by the comparative petrographic analysis of recent thin sections of Angara dams and those of 100-year-old concrete, which revealed general cement stone coalescence processes with an aggregate.